2010
DOI: 10.1016/j.bpj.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Dynamic Protein Interactions to Insulin Secretory Granule Behavior with TIRF-FRET

Abstract: Biological processes are governed by extensive networks of dynamic molecular interactions. Yet, establishing a spatial and temporal map of these interactions and their direct relationship to specific cell functions has remained a challenge. Here, we implement sensitized emission Förster resonance energy transfer (FRET) stoichiometry under total internal reflection fluorescence (TIRF) microscopy. We demonstrate through quantitative analysis and modeling that evanescent fields must be precisely matched between F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Other applications were to elucidate the role of ceramide in membrane restructuring (Ira et al 2009), the organization of bacterial light harvesting complex 2 (Dewa et al 2006), the role of cholesterol in antibody binding ), EGFR activation by EGF (Sako et al 2000;Cannon et al 2005;Teramura et al 2006), and the phase preference of peptides (Choucair et al 2007). Membrane curvature, exocytosis, and endocytosis are some other topics in which TIRF is successfully applied (Merrifield et al 2002(Merrifield et al , 2005Byrne et al 2008;Nagamatsu and Ohara-Imaizumi 2008;Joselevitch and Zenisek 2009;Ohara-Imaizume et al 2009;Aoki et al 2010;Gorg et al 2010;Lam et al 2010).…”
Section: Tirf Applications On Membrane Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other applications were to elucidate the role of ceramide in membrane restructuring (Ira et al 2009), the organization of bacterial light harvesting complex 2 (Dewa et al 2006), the role of cholesterol in antibody binding ), EGFR activation by EGF (Sako et al 2000;Cannon et al 2005;Teramura et al 2006), and the phase preference of peptides (Choucair et al 2007). Membrane curvature, exocytosis, and endocytosis are some other topics in which TIRF is successfully applied (Merrifield et al 2002(Merrifield et al , 2005Byrne et al 2008;Nagamatsu and Ohara-Imaizumi 2008;Joselevitch and Zenisek 2009;Ohara-Imaizume et al 2009;Aoki et al 2010;Gorg et al 2010;Lam et al 2010).…”
Section: Tirf Applications On Membrane Dynamicsmentioning
confidence: 99%
“…FLIM-FRET was used to detect the effect of cholesterol depletion on lipid order (Grant et al 2007) as well as dynamic protein -lipid interactions in live cells (Larijani et al 2003). TIR-FRET was used to visualize protein -protein interactions on cell membranes and insulin secreting cells (Lam et al 2010;Sohn et al 2010). Two-photon FRET was applied to visualize protein -protein colocalization (Mills et al 2003) and free versus clustered receptor-ligand complexes in the membrane (Wallrabe et al 2003).…”
Section: Applications Of Fret In Lipid Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Mature adenoviral particles were obtained and titered as described previously (33,35). Adenovirus encoding cyan fluorescent protein (cerulean)-tagged Rab27A was constructed as described above from a plasmid provided by Dr. Edward Stuenkel (36). Adenovirus encoding Xpress-tagged Rab27B wild type (WT) was a kind gift from Dr. Tetsuro Izumi (18).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies using FRET imaging under TIRF microscopy have been reported since 2003. However, all of these studies have used bimolecular FRET sensors to investigate proteinprotein interaction (Bal et al, 2008;Lam et al, 2010) or cAMP signaling (Dyachok et al, 2006). In 2006, we reported FRET imaging using the unimolecular sensor Raichu-TC10 under TIRF microscopy during EGF-induced exocytosis (Kawase et al, 2006).…”
Section: How To Use the Tirf-fret Systemmentioning
confidence: 99%